A Social Assessment Framework to Derive a Social Score for Green Material Selection: A Case Study from the Sri Lankan Cement Industry - Fernando A; Siriwardana C; Gunasekara C; Law DW; Zhang G; Gamage JCPH (MDPI (Basel, Switzerland), 2024)
Assessing the sustainability of material-based products now encompasses social sustainability, a vital aspect often overlooked. Even though the existing frameworks provide a starting point, they do not often differentiate between the assessment criteria when making comparisons within one specific material category, which has made sustainability assessments more focused on environmental and economic aspects. This study addresses this critical gap by pioneering a social assessment framework curated to help practitioners to choose the most sustainable cement type out of the standard cement types used in the industry. Utilizing the Fuzzy Analytic Hierarchy Process (FAHP) and linear-scoring method, criteria weights were systematically assigned based on scoring by industry and academic experts. The findings highlight the importance of integrating social sustainability with environmental and economic factors in cement selection. Unlike traditional material selection, which primarily considers cost and performance, green material selection emphasizes the holistic impact of materials, including social factors. Variations in weightage decisions among experts highlight the influence of practical experience, research interests, and context. Functionality emerges as a crucial criterion. The ranking of cement types based on social scores places CEM II/B-M at the top, followed by CEM IV/A, CEM II/A-S, CEM II/A-V, CEM I, and CEM II/A-LL. The evolving nature of sustainability necessitates ongoing research to refine and expand existing frameworks for a more sustainable construction industry.
Keywords: sustainability criteria; cement; material selection; FAHP; scoring method; social aspects; social impact